Mw ≥ 5 aftershocks of the 2008 Sichuan earthquake: Analysis of temporal variation of Omori Law p-value - Gupta, Harsh K.; Rekapalli, Rajesh (Frontiers in Earth Science, 2022)
Strong to great earthquakes considerably weaken the structural strength of the subsurface strata and civil constructions. The occurrence of Mw ≥ 5 aftershocks further contributes to the loss of human lives and damage to property. Therefore, the estimate of the duration of such aftershocks occurring near a metropolitan area is of major concern. In a previous study (Gupta et al., 2008), aftershocks for the destructive Sichuan earthquake, China (12 May 2008 Mw 7.9) for 23 days were used to estimate p-value and it was proposed that the M ≥ 5 aftershocks may continue for 7 months. In the present study, we analyze aftershock activity of Mw≥ 5 for 2-year duration within an area of 300 km radius from the epicenter, using modified Omori Law, which is well-known for analyzing aftershock rate and duration. We compare our results with the duration of aftershocks estimated using the exponential scaling law for the M ≥ 5 aftershock duration for major to great Himalayan earthquakes. Our analysis suggests that a high p-value (>1) indicates a slow decay of aftershocks as observed. As the p-value changes with time, the estimates of the duration of the occurrence of aftershocks of M ≥ 5 may change. Using a dynamic approach, the data of the first 100 days has been used in this study and the duration of occurrence of Mw ≥ 5 earthquakes is estimated to be ∼300 days, which is found to be true. Our analysis suggests that the temporal variation of the p-value from the onset of the mainshock and the slope of its variation are the key elements in comprehending the duration of the occurrence of the aftershocks of a certain magnitude. We infer that a high p-value (p>1) after the main earthquake, indicates a longer duration of larger aftershocks, which has been found in the case of the Sichuan earthquake. The p-value decreases with time, however, an intermittent increase in the p-value could be an indicator of an increased chance for the occurrence of a higher magnitude aftershock. The proposed dynamic approach to estimating temporal p-values may help in forecasting the occurrence of stronger aftershocks more effectively. We believe that this is the first time, where the temporal variation of p-values is estimated and related to the occurrence of aftershocks.